Artificial Intelligence in Accounting: A Systematic Literature Review and Bibliometric Analysis of Opportunities, Challenges, and Future Directions - Bakhtiar, Syamsul; Wijaya, Juli Riyanto Tri; Hidayah, Nurul (BISECER (Business Economic Entrepreneurship), 2026)
This study aims to synthesize and analyze the current state of research on Artificial Intelligence (AI) in accounting, with the objective of developing a conceptual model that demonstrates AI's influence on efficiency, accuracy, and decision-making, alongside policy recommendations for developing countries. Employing a systematic literature review of 250 Scopus-indexed journal articles published between 2015 and 2025, the research applied the keywords “artificial intelligence” AND “accounting profession” OR “financial reporting” OR “audit automation.” The selection process involved title and abstract screening, full-text evaluation, and thematic coding. Results indicate a rapid growth in publications since 2023, led by contributions from the United States, China, and India, with emerging participation from developing economies. The field is highly interdisciplinary, dominated by Computer Science and Engineering, and supported largely by public funding. The findings reveal substantial opportunities for AI to enhance operational efficiency, data accuracy, and predictive decision-making, balanced against challenges such as algorithmic bias, cybersecurity risks, and skills gaps. The study concludes that successful AI adoption in accounting requires coordinated efforts across academia, industry, and government. Implications include the need for capacity-building, cross-disciplinary collaboration, and governance frameworks to ensure equitable, ethical, and sustainable AI implementation. Keywords: Artificial Intelligence, Accounting Profession, Financial Reporting, Audit Automation, Bibliometric Analysis